The institutional framework for doing sports business: Principles of EU competition policy in sports markets - Oliver Budzinski (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2012)
The competition rules and policy framework of the European Union represents an important institutional restriction for doing sports business. Driven by the courts, the 2007 overhaul of the approach and methodology has increased the scope of competition policy towards sports associations and clubs. Nowadays, virtually all activities of sports associations that govern and organize a sports discipline with business elements are subject to antitrust rules. This includes genuine sporting rules that are essential for a league, championship or tournament to come into existence. Of course, 'real' business or commercial activities like ticket selling, marketing of broadcasting rights, etc. also have to comply with competition rules. Regulatory activities of sports associations comply with European competition rules if they pursuit a legitimate objective, its restrictive effects are inherent to that objective and proportionate to it. This new approach offers important orientation for the strategy choice of sports associations, clubs and related enterprises. Since this assessment is done following a case-by-case approach, however, neither a blacklist of anticompetitive nor a whitelist of procompetitive sporting rules can be derived. Instead, conclusions can be drawn only from the existing case decisions - but, unfortunately, this leaves many aspects open. With respect to business activities, the focus of European competition policy is on centralized marketing arrangements bundling media rights. These constitute cartels and are viewed to be anticompetitive in nature. However, they may be exempted from the cartel prohibition on efficiency and consumer benefits considerations. Here, a detailed list of conditions exists that centralized marketing arrangements must comply with in order to be legal. Although this policy seems to be well-developed at first sight, a closer look at the decision practice reveals several open problems. Other areas of the buying and selling behavior of sports associations and related enterprises are considerably less well-developed and do not provide much orientation for business.
Keywords: L83; L41; K21; D02; M21; 330; sports business; competition policy; sporting rules; centralized marketing; sports economics; Professioneller Sport; Sportmarketing; Sportökonomik; Institutionalismus; Wettbewerbspolitik; Kartellrecht; EU-Staaten